Exploring factors associated with dual tobacco smoking among people living with HIV receiving care at HIV outpatient clinics in Hanoi, Vietnam - Thanh Ha-Lan Hoang; Gloria Guevara Alvarez; Louise Adermark; Nawi Ng; Trang Nguyen; Nam Nguyen; Donna Shelley (PLoS ONE, 2025)
Background People living with HIV (PLWH) who smoke face significant health risks from tobacco use, which dual use of cigarettes and waterpipes may exacerbate due to increased nicotine exposure and dependency. This study examined the sociodemographic, behavioral, psychosocial and health-related factors associated with dual smoking among PLWH receiving care at HIV clinics in Hanoi, Vietnam. Methods This cross-sectional study used baseline survey data from the VQUIT study, an RCT of smoking cessation interventions involving 662 PLWH from 13 outpatient clinics in Vietnam. Eligible participants were current tobacco smokers; dual smokers were those using both cigarettes and waterpipes. Multivariable logistic regression was used to identify factors associated with cigarette-only and dual use among PLWH. Results Over half of the study participants were dual smokers. Dual smoking was associated with a lower annual income (aOR: 1.91, 95%CI: 1.08–3.38) and higher nicotine dependence (aOR: 2.31, 95%CI: 1.62–3.31). They were less likely to report a prior quit attempt (aOR: 0.47, 95% CI: 0.33–0.68), more likely to perceive cigarettes as more harmful (aOR 1.44, 95% CI: 1.01–2.09), and more likely to report recent illicit drug use (aOR: 2.32, 95% CI: 1.26–4.24) and longer antiretroviral treatment duration (aOR: 1.06, 95% CI: 1.03–1.10). Social support for quitting lowered the odds of dual smoking (aOR: 0.62, 95% CI: 0.39–0.97). Conclusions Dual smoking was prevalent among PLWH receiving HIV care in VQUIT study and was shaped by complex sociodemographic, behavioral, and social factors. These findings emphasize the need for integrated cessation interventions in Vietnam, where dual smoking is prevalent, particularly among PLWH. Socioeconomic status and barriers to quitting, including drug use, nicotine dependence, and tobacco-related misconceptions, should be considered. Future research should examine the long-term health impacts of dual smoking and evaluate cessation strategies for PLWH in similar settings.